2004
DOI: 10.1002/esp.1064
|View full text |Cite
|
Sign up to set email alerts
|

Landslide inventories and their statistical properties

Abstract: Landslides are generally associated with a trigger, such as an earthquake, a rapid snowmelt or a large storm. The landslide event can include a single landslide or many thousands. The frequency-area (or volume) distribution of a landslide event quantifies the number of landslides that occur at different sizes. We examine three well-documented landslide events, from Italy, Guatemala and the USA, each with a different triggering mechanism, and find that the landslide areas for all three are well approximated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

76
1,208
11
34

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,145 publications
(1,394 citation statements)
references
References 40 publications
76
1,208
11
34
Order By: Relevance
“…Frequencymagnitude relationships for different locations and landslide types are frequently considered as a proxy for landslide magnitude (van den Eeckhaut et al, 2007;Florsheim and Nichols, 2013;Malamud et al, 2004;Schlögel et al, 2011;Guzzetti et al, 2006). In order to complete the quantitative analysis of the multi-date inventory, landslide temporal probability can also be assessed using a Poisson model.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
See 2 more Smart Citations
“…Frequencymagnitude relationships for different locations and landslide types are frequently considered as a proxy for landslide magnitude (van den Eeckhaut et al, 2007;Florsheim and Nichols, 2013;Malamud et al, 2004;Schlögel et al, 2011;Guzzetti et al, 2006). In order to complete the quantitative analysis of the multi-date inventory, landslide temporal probability can also be assessed using a Poisson model.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…Two size distribution models were proposed in the literature: (1) the Double Pareto distribution (Stark and Hovius, 2001) defined by a positive and a negative power scaling, and (2) the Inverse Gamma distribution (Malamud et al, 2004) defined by a power-law decay for medium and large landslides and an exponential rollover for small landslides. According to best-fit criteria on our data, we choose a maximum-likelihood fit of the simplified version of the double Pareto (DPS) distribution defined by Eq.…”
Section: Landslide Size-frequency Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This requires knowing or assuming the relationship which describes the magnitude-frequency distribution of rockfall events in a given area characterised by specific geological and geomorphological features. For landslides, different magnitude-frequency relationships both in terms of area and volume have been used (Stark and Hovius, 2001;Guzzetti et al, 2002;Malamud et al, 2004). As to rockfalls, several authors (Hungr et al, 1999;Dussauge et al, 2003;Malamud et al, 2004) demonstrated that the magnitude-cumulative frequency (MCF) distribution of events in given volume classes j can be described by a power law in the form:…”
Section: Rockfall Frequency and Probability Of Impactmentioning
confidence: 99%
“…Recently, several studies have been carried out to determine the probability of landslide magnitude (area or volume) using frequency-area or frequency-volume statistics of landslides (Malamud et al 2004). The probability of the landslide size, in terms of it affecting an area greater or equal than a given size, can be modelled using probability density functions, as suggested by Malamud et al (2004).…”
Section: Generation Of Hsu Through Segmentationmentioning
confidence: 99%